Novel treatment options for the management of heterozygous familial hypercholesterolemia. Issue 12 (2nd December 2017) - Polychronopoulos, Georgios; Tziomalos, Konstantinos
ABSTRACT: Introduction : Even though statins represent the mainstay of treatment of heterozygous familial hypercholesterolemia (FH), their low-density lipoprotein cholesterol (LDL-C) lowering efficacy is finite and most patients with FH will not achieve LDL-C targets with statin monotherapy. Addition of ezetimibe with or without bile acid sequestrants will also not lead to treatment goals in many of these patients, particularly in those with established cardiovascular disease. In this selected subgroup of the FH population, proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors provide substantial reductions in LDL-C levels, reduce cardiovascular morbidity and appear to be safe. Mipomersen, an antisense single-strand oligonucleotide that inhibits the production of apoB by binding to the mRNA that encodes the synthesis of apoB, and lomitapide, an inhibitor of microsomal triglyceride transfer protein, also reduce LDL-C levels but are currently indicated only for the management of homozygous FH. Areas covered : In the present review, the role of PCSK9 inhibitors, mipomersen and lomitapide in the management of FH is briefly discussed. Other LDL-C-lowering agents under evaluation include inclisiran, a small interference RNA molecule that induces long-term inhibition of PSCK9 synthesis, anacetrapib, a cholesterol ester-transfer protein inhibitor, ETC-1002 (bempedoic acid), an inhibitor of adenosine triphosphate citrate lyase, and gemcabene, which reduces hepatic apolipoprotein C-III mRNA. The safety and efficacy of these agents are also reviewed. Expert Commentary : Even though several novel treatment options for heterozygous FH are under development, it remains to be shown whether these treatments will also reduce cardiovascular morbidity in these high-risk patients.